ECONOMIC AND SCALE EFFICIENCY OF BROILER PRODUCTION IN THE FEDERAL CAPITAL TERRITORY, ABUJA NIGERIA: A DATA ENVELOPMENT ANALYSIS APPROACH - Haruna E.O.; Samuel E.E.; Ibinayo B.T. (Russian Journal of Agricultural and Socio-Economic Sciences, 2020)
This study examined economic and scale efficiency of broiler production in the Federal Capital Territory, Abuja, Nigeria. Data for the study were collected from 120 broiler farmers through a multistage sampling technique with the aid of structured questionnaire as instrument for data collection. Data were analysed through the use of Data Envelopment Analysis (DEA), Ordinary Least Squares regression analysis and simple descriptive statistics. Result of the analysis revealed that the mean technical efficiency under the CRS and VRS were 0.83 and 0.88 respectively while about 3.33% and 14.17% achieved full technical efficiency under the CRS and VRS respectively. The mean allocative, economic and scale efficiency were 0.91, 0.76 and 0.94 respectively while 0.83%, 0.83% and 6.67% achieved full allocative , economic and scale efficiency respectively. The percentage of farmers that operated under the CRS, IRS and DRS were 6.67%, 85.83 and 7.5% respectively. We observed that all inputs were used above their cost minimizing quantities with feed being the highest (44.15%) followed by labour (28.98%) and then Day-old chicks (14.83%). The OLS regression results revealed that education and extension contact were negatively related to both technical and economic efficiency while household size and farming experience were positively related to them. We recommend that considerable efforts should be given to the recruitment of extension agents and training of farmers to improve their efficiency.